2021
DOI: 10.1007/s12035-021-02449-z
|View full text |Cite
|
Sign up to set email alerts
|

FAM19A5l Affects Mustard Oil-Induced Peripheral Nociception in Zebrafish

Abstract: Family with sequence similarity 19 (chemokine (C-C motif)-like), member A5 (FAM19A5) is a chemokine-like secretory protein recently identified to be involved in the regulation of osteoclast formation, post-injury neointima formation, and depression. Here, we identified FAM19A5l, an orthologous zebrafish gene that originated from a common ancestral FAM19A5 gene. FAM19A5l was expressed in trigeminal and dorsal root ganglion neurons as well as distinct neuronal subsets of the central nervous system of zebrafish. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…To validate efficiency of the sgRNA, fabp7b sgRNA and Cas9 mRNA was microinjected into one-cell wildtype embryos and genomic DNAs were extracted from circa 20 injected embryos at 24 hpf. Then, T7 endonuclease I assay was performed (Jao et al , 2013; Jeong et al , 2021). Next, homology arms of the target vector were designed by the GTagHD (http://www.genesculpt.org/gtaghd/) and the pGTag-2A-Gal4vp16-B-actin plasmid (Addgene) was used as a donor vector (Welker et al ., 2021; Wierson et al ., 2020).…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate efficiency of the sgRNA, fabp7b sgRNA and Cas9 mRNA was microinjected into one-cell wildtype embryos and genomic DNAs were extracted from circa 20 injected embryos at 24 hpf. Then, T7 endonuclease I assay was performed (Jao et al , 2013; Jeong et al , 2021). Next, homology arms of the target vector were designed by the GTagHD (http://www.genesculpt.org/gtaghd/) and the pGTag-2A-Gal4vp16-B-actin plasmid (Addgene) was used as a donor vector (Welker et al ., 2021; Wierson et al ., 2020).…”
Section: Star Methodsmentioning
confidence: 99%
“…RNA in situ hybridization was performed by alkaline phosphatase-NBT/BCIP (Roche) chromogenic reaction, as described earlier (Jeong et al ., 2021; Thisse & Thisse, 2008). The brains were rehydrated gradually through 75%, 50%, 25% methanol in 0.2 % PBST solution steps for 5 min per each solution.…”
Section: Star Methodsmentioning
confidence: 99%
“…First, the Cas9 target site in exon 1 of foxj1a gene for the single guide RNA (sgRNA) was selected using CHOPCHOP (http://chopchop.cbu.uib.no/). The sgRNA was synthesized by the cloning-free gRNA in vitro synthesis method (Wierson, Welker et al 2020, Jeong, Yun et al 2021, Welker, Wierson et al 2021, and Cas9 mRNA from the pT3TS-nCas9n vector (Addgene plasmid #46757) with mMESSAGE mMACHINE TM T3 transcription kit (Thermo Fisher). To validate the efficiency of the sgRNA, foxj1a sgRNA and Cas9 mRNA was injected into one-cell embryos and genomic DNA was extracted from the injected embryos at 24 hpf.…”
Section: Generation Of Gt(foxj1a:2a-tagrfp) Frzcc 1100 Knock-in Zebra...mentioning
confidence: 99%
“…FAM19A5, a polypeptide encoded by the TAFA5 gene located on chromosome 22 (22q13.32) in humans and chromosome 15 in mice, is primarily expressed in the brain 1 . This restricted expression and the highly conserved amino acid sequence across vertebrates suggest a crucial role for FAM19A5 in brain development and function 2,3 . A study by Huang et al (2021) showed that loss of FAM19A5 led to reduced spine density, glutamate signaling and neuronal activity.…”
Section: Introductionmentioning
confidence: 99%